Recent progress on defect modulation for highly efficient metal halide perovskite light-emitting diodes. (March 2021) - Ma, Le; Han, Boning; Zhang, Fengjuan; Xu, Leimeng; Fang, Tao; Wang, Shalong; Song, Jizhong
Highlights: We systematically analyzed the improvement of perovskite LED performance by defect modulation, from theory to experiment. We have analyzed the current mainstream defect modulation strategies and given detailed cases to confirm them. We forecast the future development based on the current development. Abstract: Metal halide perovskites (MHPs) are received widespread attention due to their high photoluminescence quantum yield (PLQY), narrow emission linewidths, tunable emission colors, and low cost. However, the non-radiative recombination loss caused by defects is a bottleneck restricting the efficiency improvement of MHP-based light-emitting diodes (PeLEDs). In this review, initially, we summarize characteristics of typical defect types that cause PeLEDs efficiency degradation, and demonstrate the effect on the carrier recombination mechanism. Then, we highlight the recent progress of typical defect suppression strategies for obtaining highly efficient PeLEDs, including crystal growth regulation, composition engineering, passivation and dimensional regulation. Finally, we look forward to the future development direction and make suggestions for how to further improve device efficiency. This review is expected to promote the development of PeLEDs and provide a significance guidance for fabricating highly efficient devices. Graphical abstract: Image, graphical abstract